QUALITATIVE ANALYSIS OF FINANCIAL REPORT EFFECTIVENESS IN STUDENT ENTREPRENEURSHIP AT UNTAG SURABAYA - Mevelia, Veronika Christine; Hwihanus, Hwihanus (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The rising interest in entrepreneurship among university students has led many to initiate their own businesses. However, these student entrepreneurs often encounter difficulties in managing their finances effectively due to inconsistent financial recording and limited digital literacy. This study aims to explore how student entrepreneurs at UNTAG Surabaya utilize financial statements to support their business financial management. Employing a qualitative case study approach, data were gathered through semi-structured interviews with student entrepreneurs across various business sectors. The findings indicate that while students recognize the importance of financial reports, particularly for monitoring cash flow and making pricing decisions, many struggle with consistency and accuracy due to academic workloads and limited time. Some participants have adopted accounting software, which improves efficiency, while others rely on manual methods. Challenges include unfamiliarity with digital tools and irregular documentation habits. The study suggests that practical accounting education and digital training are essential to improve financial reporting practices among student entrepreneurs. The results also highlight the need for universities to facilitate continuous support in integrating accounting systems into student business operations